OP0124 Mri-Based Long Term Predicition of Incident Radiographic Osteoarthritis. (10th June 2014) - Roemer, F.W.; Kwoh, C.K.; Fujii, T.; Hunter, D.J.; Boudreau, R.; Eckstein, F.; Hannon, M.J.; Guermazi, A.
Abstract : Background: Pre-radiographic structural damage is likely to increase the risk of incident radiographic osteoarthritis (ROA). It is not known, however, which specific structural changes predict incident ROA over the long-term. Objectives: The aim of the study was to determine if whether presence and severity of structural OA features delineated by MRI over up to 4 years prior to the occurrence of incident ROA (time points: P-1 = visit prior reported incidence; P-2 = two visits prior reported incidence etc.) increase the risk for incident ROA in a nested, matched case-control study based on the Osteoarthritis Initiative (OAI) cohort. A secondary aim was to assess if presence of these OA features at any of these time points increases risk of ROA. Methods: Participants were drawn from the OAI cohort (n=4796) including participants with, or at risk, of knee OA with regular yearly annual visits over 5 years. We studied 355 KL 0 and 1 knees at baseline that developed incident ROA before the 48 month visit. These were each matched 1:1 with a control knee by KL grade, gender and age within 5 years with a control knee that did not develop incident ROA. MR images were acquired at four OAI clinical centers using Siemens Trio 3 T scanners. MRIs were read for subchondral bone marrow lesions (BMLs), cartilage damage, meniscal damage and extrusion, and Hoffa- and effusion-synovitis using the MOAKS scoring system. Analyses were performed on a knee and at a compartment level (medial/lateral tibio-femoral, patella-femoral). Conditional logistic regression was used to assess the risk of incident ROA in regard to presence of large BMLs (≥2), cartilage lesions (≥1.1), meniscal tear or maceration (any), Hoffa- and effusion-synovitis (any) at P-4, P-3, P-2, P-1 or for presence at any of these time points combined. Results: Cases and controls were on average 60.1 years old (SD ±8.5), predominantly female (66.8%) and overweight (mean BMI 28.3 SD ±4.5). None of the features present at P-4 or P-3 predicted incident ROA. At P-2 only presence of Hoffa-synovitis (OR 2.31 [1.19, 4.48]), and medial meniscal damage (OR 2.44 [1.13, 5.31]), predicted OA incidence 2 years later. At P-1 Hoffa- (OR 2.42 [1.71, 3.42]), effusion-synovitis (OR 2.50 [1.76, 3.54]) and medial tibiofemoral BMLs (OR 6.50 [2.27, 18.62]) had the highest odds of incident ROA. Lateral meniscal damage or meniscal extrusion was not associated with incident ROA. Similar findings were seen for presence of these features at any of the time points with presence of large BMLs (OR 4.62 [2.89, 7.38]), effusion-synovitis (OR 3.49 [2.36, 5.15]) and cartilage damage (OR 4.00 [2.20, 7.29]) being the strongest predictors. Conclusions: Presence of structural MRI-detected joint damage 3 and 4 years prior incident ROA does not increase risk of ROA. At 2 years prior, presence of structural MRI-detected joint damage (i.e., Hoffa-synovitis or medial meniscal damage) increases risk of incident ROA. One year prior radiographic diagnosis of incident OA, presence of almost all joint features but lateral meniscal damage and any meniscal extrusion increases risk of ROA. Identification of predictors of incident ROA would allow the development of interventions to target these lesions to prevent the onset of ROA. Disclosure of Interest: F. Roemer Shareholder of: Boston Imaging Core Lab, LLC., C. K. Kwoh Consultant for: Novartis, T. Fujii: None declared, D. Hunter Grant/research support: Australia Research Council Future Fellowship, Consultant for: DonJoy, NIH, Stryker, R. Boudreau: None declared, F. Eckstein Shareholder of: Chondrometrics, M. Hannon: None declared, A. Guermazi Shareholder of: Boston Imaging Core Lab, LLC., Consultant for: Astra Zeneca, Genzyme, Novartis, Stryker, Merck Serono DOI: 10.1136/annrheumdis-2014-eular.3209